HADHANAH DALAM PRESPEKTIF IMAM MADHAB DAN KOMPILASI HUKUM ISLAM SERTA PENGARUHNYA TERHADAP PENDIDIKAN ANAK - Masadah - (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2020)
When a divorce occurs, then at that time created due to the law including the Hadhanah which is basically the responsibility of both parents who will be held accountable before God. Education is a human right which is part of economic, social and cultural rights. Likewise with a child, he has the right to obtain proper education from his parents. The pattern of hadhanah is very influential on a child's education. The house is an inseparable part of education because it starts from home. Every human being gets an initial education. Certainly, the real education provided by educators is parents in the form of care (educating). Therefore in this paper we elaborate on the hadhanah, legal basis, time, who is entitled and the conditions and how the provisions of the Hadhanah in the Compilation of Islamic Law and the Effects of Hadhanah on Children's Education. This paper is expected to provide benefits to the reader, especially for divorced couples where the child of divorce can grow psychologically as normal as other children.